Broke people, broken rules: Explaining welfare fraud investigators' attributions. (January 2021) - Headworth, Spencer
There is a notable contrast between welfare clients' and welfare fraud investigators' accounts of rule breaking behaviors. Clients describe some actions (or inactions) that constitute rule violations as accidental, and tend to attribute others to situational factors: program rules' complexity, the exigencies of day-to-day subsistence, and time and energy limitations. Fraud investigators, on the other hand, are comparatively likely to identify rule breaking as deliberate and cite clients' dispositions to explain the behavior. In part, this disparity reflects the "fundamental attribution error, " the tendency to overestimate dispositional factors' role in driving others' behavior. However, evidence from interviews with welfare fraud workers from five US states reveals the impactful administrative and normative factors that encourage them to make and assert attributions of intentionality and dispositional motivation. First, administrative priorities foreground intentional violations: federal authorities financially incentivize deliberate fraud charges, and managers favor these cases, which permit client suspensions and disqualifications. Second, emphasizing internal motivations over situational pressures serves a valuable normative function, establishing punished clients' blameworthiness and thus defending the legitimacy of both individual fraud workers and the units they compose. These findings demonstrate how policy structures and enforcement practices do not just respond to blameworthy or legally culpable behavior, but help construct narratives of blameworthiness and culpability.